Relative age effect revisited with participation trends in figure skating: did a decade make difference? - Ugurlu, A.; Bilgiç, B. (Acta Kinesiologica, 2022)
Relative age effect is a worldwide phenomenon referring to the subtle age-related (dis)advantages of athletes in the same age category, particularly in soccer and ice-hockey. Although well-established knowledge has been achieved to a certain extent, a need for further research is still valid considering different demands of each sport and possible differences in the course of time. The purpose of this study was to investigate the participation trends among elite figure skaters in the world regarding relative age effect, and to determine whether a decade has made a difference. The study sample was composed of 2313 figure skaters competing between 2009-10 and 2018-19 seasons. They were categorized into four quartiles according to their birth months. Total and season by season analyses were conducted to project any possible seasonal effect over a decade. Chi-square (÷²) goodness-of-fit tests were used to determine asymmetries in distributions, and odds ratios (OR) and 95% confidence intervals were used to compare quartiles with each other. Effect sizes were calculated using Cramer`s V (V). The results differed for disciplines and genders. Relatively older male skaters in pairs discipline were significantly over-represented (÷² = 8.528, p = 0.036, V = 0.11) and a trend favoring relatively younger skaters was determined in men`s singles discipline through the last three seasons. Season-based analyses revealed no relative age effect except for the last three seasons. In conclusion, disciplines of figure skating seem to have complex and different demands regarding relative age effect, and time seems to become a determinant for further studies.